PENERAPAN REDUCE, REUSE, RECYCLE DALAM MENDUKUNG GREEN HOTEL PADA HOUSEKEPING DEPARTEMENT DI HOTEL GRAN MELIA JAKARTA - Parantika, Asep; Azzahra , Lintang Salwa (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This study analysis the implementation of the 3R concept (Reduce, Reuse, Recycle) in the Housekeeping Department of Gran Melia Hotel Jakarta and its impact on Green Hotels. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The data were analyzed using PESTEL. The results of the study show that implementation of Reduce through reducing the use of chemicals and energy, Reuse by reusing linen and environmentally friendly cleaning equipment, and Recycle with a waste sorting system. The implementation of 3R improves operational efficiency and the image of a sustainable hotel. However, challenges such as employee awareness and program consistency are still obstacles. Further training and supervision strategies are needed to increase the effectiveness of the implementation of the 3R concept.